THE CORE SPIRITS AND VALUES OF CHRISTMAS AS DEPICTED IN “A CHRISTMAS CAROL” BY CHARLES DICKENS = TINH THẦN VÀ NHỮNG GIÁ TRỊ CỐT LÕI CỦA GIÁNG SINH TRONG TÁC PHẨM “BÀI THÁNH CA ĐÊM GIÁNG SINH” CỦA CHARLES DICKENS - Đỗ, Thị Hoa (2020)
The aim of this thesis is to investigate and identify the core spirits and values of Victorian Christmas and to make a comparison between Christmas in the Victorian era and that in modern times. In the first part, the sacrosanct and the atmosphere of Christmas are presented. These show that Victorian Christmas and its spirit were a carol revealing society’s attitudes toward reality. The thesis then identifies the core values of Victorian Christmas, and further discusses the significance of the above spirit and values in modern society. In the main section, the thesis provides readers with the analysis of vividly religious rituals in celebration through numerous Christmas scenes. At the same time, readers are well aware that the commemoration was for family reunification, and the balance between materials and humanity. In conclusion, the thesis indicates that Christmas is an integral part with Christian people by its profound spirits and values spreading within society at any times. This thesis hopes to give readers a different perspective of Christmas through a book written in the 19th century, and ultimately make a small contribution to getting people of different religions aware of the basis of Christmas as a universal festival.